Comparative study between the use of brix-3000 and the rotational conventional technique against tooh decay - Varea Torresi, Fernando; Freire Acosta, Margarita (Horizonte Sanitario, 2019)
Objective: to verify the effectiveness of the papaine-based enzymatic gelBRIX-3000, following the procedure for the atraumatic removal of carious lesions established by the manufacturers. Materials and methods:This is a descriptive and comparative study based on papain gel application through longitudinal cut. This procedure was performed in 150 previously selected patients of both sexes between the ages of 5 to 12 years. The comparative group consisted of 31 children of both sexes with active caries who were treated with the conventional rotary technique. After the treatment given, patients were categorized on a numeric scale from 0 to 3, where Grade 0 refers to patient’s asymptomatic status, grade 1 when patient’s treated piece presented mild sensitivity to thermal stimuli (cold or hot), Grade 2 representspatient’s moderate pain and Grade 3 corresponds to patient’s severe pain. Patients were controlled at 8, 15, and 30 days after receiving the initial treatment with papain gel. Results: 88.70% of patients treated with papaine-based enzymatic gelBRIX-3000presented grade 0 (asymptomatic) at 30 days after treatment, whereas 58.10% of patients treated with the conventional rotary techniquepresented grade0. Conclusion:There is a higher level of effectiveness in the removal of carious lesions when using papaine-based enzymatic gelBRIX-3000 in comparison with the conventional rotary technique. Keywords: Atraumático; removal; cárie; enzymatic, brix-3000.